High-Energy Burst-Mode 3.5 μm MIR KTA-OPO - Haowen Guo; Chunyan Jia; Shuai Ye; Yongping Yao; Tiejun Ma; Jiayu Zhang; Meng Bai; Jinbao Xia; Hongkun Nie; Bo Yao; Jingliang He; Baitao Zhang (Photonics)
In this paper, a high energy 3.5 μm mid-infrared (MIR) burst-mode KTA optical parametric oscillator (OPO) was demonstrated. Utilizing a quasi-continuous wave (QCW) laser diode (LD) side-pump module and electro-optic (EO) Q-switching technique, a high beam quality 1064 nm burst-mode laser was achieved as the fundamental source, generating 30 mJ high-energy pulses at burst repetition rates of 100 Hz and 200 Hz with sub-burst repetition rates of 20 kHz, 40 kHz, and 50 kHz. The KTA-OPO produced a 3.5 μm MIR burst-mode laser output with 4 to 11 sub-pulses per pulse envelope. The output energies were 2.9 mJ, 2.81 mJ, and 2.79 mJ at 100 Hz, as well as 2.8 mJ, 2.75 mJ, and 2.72 mJ at 200 Hz, with corresponding conversion efficiencies of 9.6%, 9.3%, and 9.3% at 100 Hz, as well as 9.3%, 9.2%, and 9.1% at 200 Hz, respectively. Our results pave a new way for generating burst-mode MIR lasers.